Effectiveness of a Proposed Strategy Based on the Cognitive Integration Approach in Developing Enlightened Thinking among First-Year Sociology Students in the Philosophy Course - Khamis, Prof. Dr. Tareq Hashim Khamis (Sulaimani Journal for Humanities, 2026)
This study aims to identify the effectiveness of a proposed strategy based on the cognitive integration approach in developing enlightened thinking among first-year students of the Sociology Department in the Philosophy course. The researcher developed this new strategy according to the theoretical foundation of the cognitive integration approach, which represents the connection between a group of humanities-related sciences.The researcher constructed an enlightened thinking test and verified its validity and reliability. The research instruments were presented to a panel of experts and referees to confirm their suitability, achieving an agreement rate exceeding 80%. The researcher ensured equivalence between the study groups based on gender (male, female) and the academic achievement of the father.The research sample included 60 students randomly selected from the first year. The research groups were divided randomly: Group A, consisting of 30 students, formed the control group, while Group B, consisting of 30 students, formed the experimental group. The researcher taught both groups personally. After statistical processing and data analysis, the results indicated a significant increase in the level of enlightened thinking in the experimental group compared to the control group.Based on the results, the researcher provided a number of recommendations and conclusions, including the provision of an appropriate educational environment—especially in university studies—to apply theoretical knowledge practically, enabling students to better express their inclinations, abilities, and productive cognitive skills.
Keywords: Strategy; Proposed; Thinking; Enlightened; Sociology